Analisis Penggunaan Three NOs oleh Korea Selatan untuk Mengatasi Boikot di Cina Akibat Terminal High Altitude Area Defense (THAAD) - Permatasari, Decyani; Wahyudi, Fendy Eko (Journal of International Relations, 2019)
In July 2016, South Korea agreed with US to install the Terminal High Altitude Area Defense (THAAD) in its territory. This agreement rejectedby China which considered the instrument would disrupt its sovereignty and is only US's way to instill its influence in East Asia Region. China's resistance has led to boycotts of South Korean cultural industry cluster. The issue surrounding THAAD was ended after South Korean Foreign Minister stated her position on China's concern. South Korea issued a statement about Three NOs, namely: 1) no additional THAAD deployment; 2) no participation in US‟s missile defense network; and 3) no establishment of a trilateral military alliance with US and Japan. A day later, China issued a statement regarding the normalization of relations with South Korea. This study aims to determine the cause of South Korea agreed on Three NOs in normalizing relations with China. This study uses theory of interdependencewith linkage strategy. The method used is qualitative with explanatory type. As a result, Three NOs is a form of exchange of issues so that boycotts can be stopped. This was motivated by South Korea's interdependence on its cultural industry cluster and China. South Korea‟s strategy is said to be successful because it provides a win-win solution for two countries.